2022
DOI: 10.3390/ijerph19095420
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Risk, Work, and Lifestyle Changes on Mental Health of Healthcare Workers Amidst the COVID-19 Pandemic

Abstract: The COVID-19 outbreak is significantly affecting the mental health of healthcare workers worldwide. This study aims to investigate the mental health outcomes of healthcare workers in a health system located in southeastern US during the first peak of the pandemic and examine the association of specific factors on the mental well-being of healthcare workers. A cross-sectional survey of 388 healthcare workers was conducted. Data were collected using a 79-item questionnaire, which included the Patient Health Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…209 articles continued to the full text screening stage, of which 119 studies were selected for inclusion in our meta-analysis with a total of 117,143 participants ( Table 1A ). All 119 studies were cross-sectional observational studies ( Agberotimi et al., 2020 ; Alah et al., 2021 ; Ali et al., 2020 , 2022 , 2021 ; Alonso et al., 2021 ; Alshehri and Alghamdi, 2021 ; Asnakew et al., 2021 ; Ayalew et al., 2022 ; Azoulay et al., 2021 ; Bassi et al., 2021 ; Benzakour et al., 2022 ; Bizri et al., 2022 ; Bonzini et al., 2022 ; Bulut et al., 2021 ; Caillet et al., 2020 ; Caliandro et al., 2022 ; Carmassi et al., 2022 , 2021a , 2021b ; Chang et al., 2022 ; Chan et al., 2021 ; Chatzittofis et al., 2021 ; Chaudhary et al., 2021 ; B. Chen et al., 2022 ; Cheng et al., 2020 ; Chen et al., 2021 ; Chew et al., 2020 ; Chowdhury et al., 2021 ; Civantos et al., 2020a , 2020b ; Cortés-Álvarez and Vuelvas-Olmos, 2020 ; Costantini et al., 2022 ; Crowe et al., 2022 ; Demartini et al., 2020 ; Dobson et al., 2021 ; Dykes et al., 2022 ; Ergai et al., 2022 ; Essadek et al., 2022 ; Fattori et al., 2021 ; Geng et al., 2021 ; Gilleen et al., 2021 ; Gorini et al., 2020 ; Guo et al., 2021 ; Hajure et al., 2021 ; Hasanvandi et al., 2022 ; Honarmand et al., 2022 ; Hong et al., 2021 ; Huarcaya-Victoria et al., 2022 ; …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…209 articles continued to the full text screening stage, of which 119 studies were selected for inclusion in our meta-analysis with a total of 117,143 participants ( Table 1A ). All 119 studies were cross-sectional observational studies ( Agberotimi et al., 2020 ; Alah et al., 2021 ; Ali et al., 2020 , 2022 , 2021 ; Alonso et al., 2021 ; Alshehri and Alghamdi, 2021 ; Asnakew et al., 2021 ; Ayalew et al., 2022 ; Azoulay et al., 2021 ; Bassi et al., 2021 ; Benzakour et al., 2022 ; Bizri et al., 2022 ; Bonzini et al., 2022 ; Bulut et al., 2021 ; Caillet et al., 2020 ; Caliandro et al., 2022 ; Carmassi et al., 2022 , 2021a , 2021b ; Chang et al., 2022 ; Chan et al., 2021 ; Chatzittofis et al., 2021 ; Chaudhary et al., 2021 ; B. Chen et al., 2022 ; Cheng et al., 2020 ; Chen et al., 2021 ; Chew et al., 2020 ; Chowdhury et al., 2021 ; Civantos et al., 2020a , 2020b ; Cortés-Álvarez and Vuelvas-Olmos, 2020 ; Costantini et al., 2022 ; Crowe et al., 2022 ; Demartini et al., 2020 ; Dobson et al., 2021 ; Dykes et al., 2022 ; Ergai et al., 2022 ; Essadek et al., 2022 ; Fattori et al., 2021 ; Geng et al., 2021 ; Gilleen et al., 2021 ; Gorini et al., 2020 ; Guo et al., 2021 ; Hajure et al., 2021 ; Hasanvandi et al., 2022 ; Honarmand et al., 2022 ; Hong et al., 2021 ; Huarcaya-Victoria et al., 2022 ; …”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies that reported study population in more detail, 28,365 (25.2%) were physicians, 48,171 (42.8%) were nurses, 13,903 (12.4%) were allied health professionals, 10,029 (8.9%) were auxiliary health professionals, and 12,103 (10.8%) participants were specified as “other”. Four (4) studies specified the breakdown of their study population by profession, but used different categories that did not allow us to fully separate the data for our analysis ( Collantoni et al., 2021 ; Ergai et al., 2022 ; Riello et al., 2020 ; Van Wert et al., 2022 ). Table 1 summarizes this data.…”
Section: Resultsmentioning
confidence: 99%
“…4 Finally, almost 42% of HCWs reported feeling fearful about COVID-19 and had anxiety related to becoming infected themselves and/or infecting a loved one. 2 Predictors of HCWs’ mental health symptoms during COVID-19 included younger age, 3,6,7 female gender, 5,79 fear of COVID-19 transmission/family exposure, 7,10 being at very high risk for COVID-19, 6 profession 11,12 and a history of mental health disorders. 13,14…”
Section: Introductionmentioning
confidence: 99%
“…4 Finally, almost 42% of HCWs reported feeling fearful about COVID-19 and had anxiety related to becoming infected themselves and/or infecting a loved one. 2 Predictors of HCWs' mental health symptoms during COVID-19 included younger age, 3,6,7 female gender, 5,[7][8][9] fear of COVID-19 transmission/ family exposure, 7,10 being at very high risk for COVID-19, 6 profession 11,12 and a history of mental health disorders. 13,14 Although calls for HCW mental health support arose following the severe acute respiratory syndrome global outbreak, 15 there is little consensus in the literature on how to best support HCWs' mental health.…”
Section: Introductionmentioning
confidence: 99%
“…The spread of COVID-19 has changed many aspects of people’s lives, including individual social behavior, 4 - 6 and healthcare procedures. 7 , 8 It has also altered physiological, 4 , 6 , 9 - 13 as well as pathophysiological responses. 14 , 15 There is a possibility that some medical studies may be influenced by one or more hidden powers brought about by the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%